Implementation of computers in schools: a case study of five schools in the Makana and Somerset East districts - Prince, Gilbert Leslie (Rhodes University, Faculty of Education, Department of Education, 2007)
This case study attempts to explain the implementation of Information Communications Technology (ICT) in primary schools, specifically mentioning the integration of computers into the curriculum. To begin with, the implementation of ICT from an international perspective is explored and subsequently some international and African ICT policies in education are also identified and discussed. Nationally, ICT policies from four provinces in South Africa are examined and analyzed. Provincially, the ICT Projects Coordinator in the Eastern Cape Department of Education (ECDoE) was interviewed to obtain a provincial perspective of ICT in the Eastern Cape. From local schools' perspective, four primary schools and one secondary school in the Makana and Somerset East Districts were visited and the ICT coordinators at these schools were interviewed. The results reveal that the previously disadvantaged (PD) schools were not utilizing their computers effectively. This is due to a number of factors, including a lack of funds to maintain the computers; unskilled or under skilled teachers in ICT; and under resourced computer facilities. The previously advantaged (PA) schools, on the other hand, have well-resourced computer laboratories, adequate maintenance plans as well as skilled teachers in ICT that enable these schools to effectively integrate the use of computers into the curriculum. Key words: Information communications technology, implementation, integration, previously advantaged, previously disadvantaged, curriculum, primary school, secondary school.
Keywords: Educational technology; Educational technology -- South Africa -- Eastern Cape; Education, Elementary -- Computer-assisted instruction; Computer-assisted instruction -- South Africa -- Eastern Cape; Computer managed instruction -- South Africa -- Eastern Cape; Internet in education -- South Africa -- Eastern Cape